Fungi from a groundwater-fed drinking water supply system in Brazil - Oliveira, Helena M. B. (2016)
Filamentous fungi in drinking water distribution systems are known to (a) block water pipes; (b) cause organoleptic biodeterioration; (c) act as pathogens or allergens and (d) cause mycotoxin contamination. Yeasts might also cause problems. This study describes the occurrence of several fungal species in a water distribution system supplied by groundwater in Recife, Pernambuco, Brazil. Water samples were collected from four sampling sites from which fungi were recovered by membrane filtration. The numbers in all sampling sites ranged from 5 to 207 colony forming units (CFU)/100 mL with a mean value of 53 CFU/100 mL. In total, 859 isolates were identified morphologically, with Aspergillus and Penicillium the most representative genera (37% and 25% respectively), followed by Trichoderma and Fusarium (9% each), Curvularia (5%) and finally the species Pestalotiopsis karstenii (2%). Ramichloridium and Leptodontium were isolated and are black yeasts, a group that include emergent pathogens. The drinking water system in Recife may play a role in fungal dissemination, including opportunistic pathogens.